Estimated glomerular filtration rate and drug dose adjustment in patients in an intensive care unit in Brazil - Marianne Silveira Camargo; Márcio Galvão Oliveira; Sostenes Mistro; Izabel Cristina Pereira Rocha; Camila Neto Santos; Caroline Tianeze de Castro; Luiz Carlos Santana Passos (Universidade de São Paulo, 2020)
Objectives. This study sought to compare the estimated glomerular filtration rate and the indication of dose adjustment of antimicrobials when using Cockcroft-Gault or Modification of Diet in Renal Disease. Methods. A cross-sectional study was performed with patients admitted to the intensive care unit of a Brazilian general hospital. The glomerular filtration rate was calculated for patients on all days using the Cockcroft-Gault and Modification of Diet in Renal Disease equations. The difference in estimated glomerular filtration and the dose adjustment indication of antimicrobials were assessed. Results. A total of 631 patients were included in this study. The median estimated glomerular filtration was significantly higher when estimated using Modification of Diet in Renal Disease (100.3 mL/ min/1.73 m2) than the estimation by Cockcroft-Gault (83.2 mL/min) [p<0.001]. Greater differences in estimations produced by the two formulae were observed in patients at extremes of weight and age, and a different dose adjustment was indicated for all antimicrobials assessed. Conclusions. These results demonstrate a significant difference in estimated glomerular filtration rate values when calculated using either Cockcroft-Gault or Modification of Diet in Renal Disease as well as in the indication of dose adjustment in an intensive care unit.